Indicadores de empatia em crianças com baixa visão e em seus pais : um estudo de caso - Godoy, Ana Maura Azevedo de (2007)
Empathy is important in the maintenance interpersonal relationships, and cam be considered a behavior protective factor for behavior problem. This work is aimed at describing and evaluating empathy in two sisters with low eyesight, one of them is nine and the other one is 11 years old and of their parents, in a attempt to: 1. identify subclasses of empathical abilities present in the repertoire of the children; 2. characterize similarities and differences in the frequency of children s empathy subclasses; 3. evaluate the father s and mother s level of empathy; 4. characterize similarities and differences between the father s and mother s educational actions. The instruments utilized were: a structured interview script with the parents, empathy inventory (EI), stories that were printed and recorded in audio and semi-structured interviews with the children. The parents answered both the interview individually, which was recorded, and the empathy inventory (EI) with the researcher s help. With the children, the researcher developed three activities which were filmed: present printed stories, stories in audio and interview the children in an attempt to investigate the recognition of the situation and the emotions of the characters in a specific situation. Data obtained from the interviewed parents and the children were analyzed qualitatively, and the (EI) provided quantitative results. Results indicate that parents present a high frequency of overprotective behavior, intercalated with granted autonomies in domestic activities and in requests made by the children. The father s report was different from the mother´s, who answers may be a result of her beliefs about the development of her daughters. The (EI) showed that the mother is more empathic than the father. With regard the results obtained with the children, they suggest that they present behaviors that are indicative of empathy, and that they also identify and understand the emotions of joy, sorrow, fear and disgust presented by the characters of the stories.